Forage potential of sorghum-clover intercropping systems in semi-arid conditions - Ashoori,Naghmeh (2021)
ABSTRACT To identify the optimum intercropping system of sorghum and clover in terms of quantity and quality of forage yield, a two-year experiment was conducted in a semi-arid region of Iran, during the 2016 and 2017 growing seasons. Treatments consisted of eight cropping systems: S75C25 (75% sorghum + 25% clover), S50C50 and S25C75, as replacement series; S100C50, S50C100, and S100C100 as additive series; and sole cultures of sorghum and clover. The highest and lowest dry matter (DM) yield (29.17 and 10.71 Mg·ha-1) were found in the S100C100 and clover monoculture systems, respectively. Although the highest content of crude protein (CP) and digestible dry matter (DDM) were recorded from clover monoculture, the maximum yield of CP and DDM were obtained from the S100C100. Increasing the proportion of clover in intercropping decreased the acid detergent fiber and neutral detergent fiber, increased the relative feed value, net energy for lactation and dry matter intake. Increasing the proportion of sorghum in intercropping improved the yield of DM, CP and DDM. The land equivalent ratio for DM yield was higher than one in all intercropping treatments but were significantly higher in the additive intercropping systems. Overall, it could be concluded that sorghum and clover additive intercropping systems increased forage yield and quality, however if simultaneous increase of the quantity and quality of forage is the interest of this study then the S100C100 system had a significant advantage over other treatments and can be a suitable alternative for sorghum and clover monoculture systems in semi-arid regions.